Pendampingan Pendampingan Kegiatan Posyandu di Desa Bandarkedungmulyo dalam Meningkatkan Persentase Kesehatan Serta Memberikan Sarana Pencegahan Penularan Covid-19 - Mohammad Saat Ibnu Waqfin; Aimmatul Fitriyah; Kholidatuzzuhriyah Kholidatuzzuhriyah; Anton Muhibuddin (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
National development in the health sector through posyandu is the development of human resources for the purpose of optimizing the degree of public health as measured by the Maternal Mortality Rate (MMR) per 100,000 live births and the Infant Mortality Rate (IMR) per 1000 live births which are also components of the Human Development Index (HDI). . The goal of posyandu is to reduce the Maternal Mortality Rate (MMR) and the Infant Mortality Rate (IMR) in Indonesia through community empowerment efforts. The targets of the posyandu are all babies, toddlers, pregnant women, breastfeeding mothers, post-partum mothers as well as women at fertile age (WUS) and fertile age couples (PUS). Posyandu activities consist of maternal and child health (KIA), family planning (KB), immunization, improved nutrition, prevention and overcoming diarrhea. Posyandu has a human development linkage, this linkage can be seen from the efforts to reduce MMR and IMR in Indonesia, while in Indonesia MMR and IMR are still very high, this is due to the failure to achieve the 2015 MDG'S target to overcome this problem, it is necessary to revitalize posyandu and implement good management at posyandu so that provide a solution to the AKI and AKB problems. The goal of posyandu to reduce MMR and IMR is to increase life expectancy in Indonesia. If the life expectancy of humans in Indonesia increases it means that the quality of human life will be better so that it can improve the quality of human development from sharing sides nationally in Indonesia.